PELAKSANAAN IZIN USAHA MIKRO KECIL DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Pratama, Hengky; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Based on the Regulation of the Mayor (Perwako) of Pekanbaru Number 96 of 2015 concerning the Implementation of Small Micro Business Licenses from the Mayor to the Camat, the District of Rumbai Pesisir has decreased the number of issuance and extended the Small Micro Business License. The purpose of this study is how the Implementation of Small Micro Business Licensing in the District of Pekanbaru City Rumbai Pesisir and to find out the Inhibiting Factors of the Implementation of Small Micro Business Licenses in the District of Rumbai Pesisir Kota Pekanbaru. The theoretical concept used by the author is Implementation. The researcher used qualitative research with descriptive studies. In collecting data, the author uses interview and observation techniques. The author uses informants as information as a source of data validity. The results of this study indicate that the Implementation of Micro Small Business Licenses is still not maximal, it is evidenced that there are still a number of micro and small business licenses issued in Rumbai Pesisir District. Inhibiting Factors Implementation of the Micro Small Business License in Pekanbaru in the District of Rumbai Pesisir, Pekanbaru City includes Development and Socialization and Evaluation.Keywords: Implementation, Coastal District